NPM1 mutations define a specific subgroup of MDS and MDS/MPN patients with favorable outcomes with intensive chemotherapy - Montalban-Bravo, Guillermo (Blood Adv, 2019)
Nucleophosmin (NPM1) mutations are common in acute myeloid leukemia and are associated with high remission rates and prolonged survival with intensive chemotherapy. NPM1 mutations are rare in myelodysplastic syndromes (MDS) or myelodysplastic/myeloproliferative neoplasm (MDS/MPN), and the clinical outcomes of these patients, when treated with intensive chemotherapy, are unknown. We retrospectively evaluated the clinicopathologic characteristics and the impact of therapy in 31 patients with MDS or MDS/MPN and NPM1 mutations. Next-generation sequencing was performed at diagnosis in 22 patients. Median age was 62 years (range, 19-86). Twenty-four patients (77%) had normal karyotype, and all had multilineage dysplasia. Most patients could be classified as MDS with excess blasts (19/31, 61%). NPM1 mutations were detected at a median allele frequency of 0.38 (range, 0.09-0.49). Mutation burden did not correlate with bone marrow blast frequency, and its clearance seemed to be associated with decreased morphologic dysplasia. Ten of the 31 patients (32%) received cytotoxic chemotherapy, 20 (65%) hypomethylating agents, and 1 (4%) lenalidomide. Sequential sequencing was available in 16 (52%) patients, and mutation burden correlated with disease status and response to therapy. Patients treated with chemotherapy had higher complete response rates (90% vs 28%, P = .004), longer median progression-free survival (not reached vs 7.5 months, P = .023), and overall survival (not reached vs 16 months, P = .047). Intensive chemotherapy and allogeneic stem cell transplantation (SCT) may be associated with improved clinical outcomes in patients with NPM1-mutated MDS or MDS/MPN who are candidates for this form of therapy.